Levels of shading and application of glyphosate and carfentrazone-ehyl in the control of Macroptilium atropurpureum - Costa, Gustavo A.; Santos, Leonardo D. T.; Ferreira, Guilherme A. de P.; Cruz, Leandro R. da [UNESP]; Machado, Vitor D.; Rocha, Leonardo M. (Univ Federal Campina Grande, 2018)
Variations in environmental conditions, such as the availability of light, can affect the efficacy of herbicides because they alter the biological characteristics of plants including those that are related to the plant's sensitivity to herbicides. Therefore, the objective of the present study was to assess the influence of environments with different light availabilities, and of the application of glyphosate and carfentrazone-ethyl (separately or in combination) on the morphophysiology and control of Macroptilium atropurpureum. An experimental design of randomized blocks with five replicates was used, with treatments arranged in a split-plot design. The plots were composed of three levels of shading (full sunlight, 50% shading, and 70% shading); within each plot there were sub-plots, one for each of the two herbicides (glyphosate and carfentrazone-ethyl), used either separately or in combination. The doses of gtyphosate + carfentrazone- ethyl applied in the treatments were 0+40 g ha(-1) of carfentrazone-ethyl, 1.440+0 g ha(-1) of glyphosate, 1.080+30 g ha(-1 )of glyphosate + carfentrazone-ethyl, and there was an additional - treatment that did not include the application of an herbicide. Plants of M. atropurpureum cultivated under shading exhibited higher sensitivity to the herbicides, greater leaflet area, and lower photosynthetic rates than plants cultivated under full sunlight conditions. Under shading, both herbicides applied separately or in combination were effective in controlling M. atropurpureum, which indicates a greater susceptibility of this species to these herbicides in environments with light restriction. The species was tolerant to the two tested herbicides, used either alone or in combination, when grown under full sunlight conditions.
Keywords: physiology; siratro; photosynthetic rate; leaf area